AFM surface analysis of Fe–Co–Mo electrolytic coatings - Yermolenko, I. Yu.; Ved, M. V.; Sakhnenko, N. D.; Zubanova, S. I.; Tychyna, O. N. (Інститут хімії поверхні ім. О. О. Чуйка НАН України, 2017)
The study aims at the investigation of the morphology and topography of the ternary Fe–Co–Mo electrolytic coatings. Compositions and morphology of the alloys are examined by scanning electron microscopy and X-ray analysis. Both topography and surface roughness are studied by an atomic force microscopy AFM using a NT–206 microscope. The Fe–Co–Mo coatings with an iron content of 47 at.%, cobalt 28 at.% and molybdenum 25 at.% are deposited on mild steel substrate by pulse electrolysis mode from citrate bath with the ratio of concentrations с(Fe³⁺):с(Co²⁺):с(MoO₄²⁻) = 2.5:3:1. Atomic force microscope analysis topography of the coatings Fe–Co–Mo at the scanning area 39.9×39.9 μm show that their surface is more developed compared with the substrate material. Moreover the AFM analysis of the coatings morphology and surface topography indicates the parts with a globular structure with an average conglomerates size of 0.2-0.5 μm and singly located sharp grains. Within the same scan area, sites with a developed surface are detected the topography of which is identical to the crystal structure of cobalt with the crystallite size in the range of 0.2-1.75 μm. The parameters Ra and Rq for parts with different morphology as well as average characteristics of coatings demonstrated the low roughness of the surface. Electrolytic deposits Fe–Co–Mo can be attributed to 8-9-th class of roughness. The study tested the magnetic behavior of Fe–Co–Mo coatings. The coercive force of 7-10 Oe confirms the soft magnetic properties of materials which in combination with high microhardness open prospects for usage of Fe–Co–Mo systems in the production of magnetic head elements for recording and reproducing information.
Keywords: pulse electrolysis; magnetic properties; morphology; ternary alloys; topography